(untitled) (Bolton, Masachusetts, 2000)
This book is divided into three sections: organizational change in the academy and in POD, collaboration and partnerships and examining assumptions about teaching and faculty development.
Keywords: Universities and colleges,College teachers,College teaching,Universities and colleges; Planning,Faculty